The prevalence, severity, and risk factors of erosive esophagitis in a Middle Eastern population - Majid Alsahafi; Fatma Salah; Hebah Mimish; Mohammed Hejazi; Resheed Alkhiari; Saad Alkhowaiter; Mahmoud Mosli (The Saudi Journal of Gastroenterology)
Background: Erosive esophagitis (EE) is frequently present in patients with gastroesophageal reflux disease (GERD), some of which may not have GERD symptoms. The prevalence of EE in the Saudi population is unknown. In this study, we aimed to determine the prevalence and risk factors of EE among patients undergoing esophagogastroduodenoscopy (EGD). Methods: We retrospectively reviewed consecutive adults who underwent EGD at an academic tertiary care center. Clinical and endoscopic data were collected. The prevalence and severity of EE were determined. Multivariate regression analysis was used to identify risk factors for EE. Results: Records for 3230 patients were reviewed, of which 2805 were included in this study. The mean age was 48.6 ±18.6 years, and 1088 (38.7%) were male. Two hundred and twenty six (8%) patients underwent EGD for GERD-related indications. EE was noted in 309 (11%) patients and 58 (25.6%) with GERD-related indications. For patients with EE, the mean age was 49.2 ± 18.7 years, and 132 (42.7%) were males. LA Grade A esophagitis was the most common (53.9%), followed by grade B (29.6%). Among all patients, only EGD for GERD-related indications and hiatal hernia were significantly associated with EE on multivariate analysis [(aOR = 3.1, 95% CI 2.2–4.4, P < 0.01) and (aOR = 1.4, 95% CI 1.1–1.9, P < 0.01), respectively]. Age, gender, and body mass index were not associated with EE. Conclusion: In this large cohort, EE was present in 11% of patients who underwent EGD and in 25% of patients with GERD. EGD for GERD-related indications and hiatal hernia are independent risk factors for the presence of EE.